2009
DOI: 10.1016/j.acap.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Enrollment of Eligible Extremely-Low-Birth-Weight Children in the Part C Early Intervention Program

Abstract: Objective To determine whether eligible extremely-low-birth-weight children (<1000 g) were enrolled in the federally enacted, state-coordinated Early Intervention (EI) program intended to help children with developmental delay or disability regardless of parental income, and the factors associated with enrollment. Methods Retrospective analysis of 884 EI-eligible ELBW children born in South Carolina with birth weight 401 to 999 g, gestation ≥24 weeks, and survival for the first 120 days of life. We created a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 19 publications
4
36
4
Order By: Relevance
“…[17][18][19][20] In one (4) 1 (1) 5 (14) 1 (2) 30 (2) Referred to EI + OTH 14 (2) 5 (2) 17 (21) 11 (31) 3 (5) 50 (4) Referred to OTH 104 (14) 46 (13) 34 (41) 7 (20) 5 (9) population-based study of nationally represented children, only 10% of developmentally delayed children received EI at 24 months. 19 The current study is the first, to our knowledge, to look at EI referral rates among a population of high-risk infants after NICU discharge.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] In one (4) 1 (1) 5 (14) 1 (2) 30 (2) Referred to EI + OTH 14 (2) 5 (2) 17 (21) 11 (31) 3 (5) 50 (4) Referred to OTH 104 (14) 46 (13) 34 (41) 7 (20) 5 (9) population-based study of nationally represented children, only 10% of developmentally delayed children received EI at 24 months. 19 The current study is the first, to our knowledge, to look at EI referral rates among a population of high-risk infants after NICU discharge.…”
Section: Discussionmentioning
confidence: 99%
“…17,25,26 Wang et al 20 reported higher EI enrollment among children with birth weights ,1000 g who were receiving public insurance. Results from our regression analyses also showed that EI referrals were positively associated with public insurance.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors were chosen based on factors that other studies have investigated or recommended for future studies with regards to follow-up adherence. The risk factors were the age 16 and gender 15,16,18,19,[33][34][35] of the child, maternal and caregiver age [15][16][17]19,21,23,35,36 , who the primary caregiver is, marital status of caregivers 19,20,37 , educational qualifications [15][16][17][18][19][20]23,35,36 , employment 18,20,35 , average household income [16][17][18][19][20]33,35,36 , type of housing 18 and number of people living in the household 35 . In addition, the effect of text message reminders on follow-up adherence was investigated 22,38 .…”
Section: Risk Assessment Questionnairementioning
confidence: 99%
“…Comprehensive tracking and follow-up systems are however required to ensure that children are not only identified through screening, but also return for the appropriate assessments and intervention 14 . Various studies have, however, reported poor follow-up adherence for children who were referred for an early intervention evaluation [15][16][17][18] . Low participation rates lead to diminished effectiveness of early intervention programmes 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation